FARM TECHNOLOGY IMPROVEMENT AND ITS IMPACT ON SOCIAL NORMS: A STUDY OF ALIGARH DISTRICT (UTTAR PRADESH) - Rana, Tejbir Singh; Sharma, Arti; Ratnu, Bharat (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research article is based primarily on primary data. During a field visit to the Aligarh district, 400 household samples were collected to know the level of technology penetration in the agricultural farms. Both urban and rural household samples were analyzed to find out the exact level of ownership regarding farm machines. It has been found that most of the agricultural farm machines are owned by rural people. Few urban households were found owning farm machines, but these households were in the tehsil towns. As per the definition of the Census of India, tehsil towns are considered urban areas. The subsequent results have been discussed in this article.